Assessment of the traffic energy consumption based on a city transportation model - Nikolić Ana M.; Đorić Vladimir D. (Tehnika, 2016)
Sustainable use of energy is required to ensure that future generations have the energy sources, which enable them to the minimum quality of life that the current generation has. Transport is one of the largest consumers of energy and a source of significant influence on the environment through pollution. This paper presents the usage of the transportation model for the modal shift from motorized means of transportation to cycling, as well as an overview of measures for saving energy. In addition, it presents a modal transport method for the modal shift from the motorized modes of transport to cycling. Also, the method for quantifying energy in transport is presented. It is based on the shortest path using network load 'all or nothing', in which the incremental network load is used. The focus is on the modal shift from motorized transport modes to bicycle traffic and its impact on energy savings.